General characterization of Tityus fasciolatus scorpion venom. Molecular identification of toxins and localization of linear B-cell epitopes - Mendes, T. M.; Guimaraes-Okamoto, P. T. C. [UNESP]; Machado-de-Avila, R. A.; Oliveira, D.; Melo, M. M.; Lobato, Z. I.; Kalapothakis, E.; Chavez-Olortegui, C. (Elsevier B.V., 2015)
This communication describes the general characteristics of the venom from the Brazilian scorpion Tityus fasciolatus, which is an endemic species found in the central Brazil (States of Goias and Minas Gerais), being responsible for sting accidents in this area. The soluble venom obtained from this scorpion is toxic to mice being the LD50 is 2.984 mg/kg (subcutaneally). SDS-PAGE of the soluble venom resulted in 10 fractions ranged in size from 6 to 10-80 kDa. Sheep were employed for anti-T. fasciolatus venom serum production. Western blotting analysis showed that most of these venom proteins are immunogenic. T. fasciolatus anti-venom revealed consistent cross-reactivity with venom antigens from Tityus serrulatus. Using known primers for T. serrulatus toxins, we have identified three toxins sequences from T. fasciolatus venom. Linear epitopes of these toxins were localized and fifty-five overlapping pentadecapeptides covering complete amino acid sequence of the three toxins were synthesized in cellulose membrane (spot-synthesis technique). The epitopes were located on the 3D structures and some important residues for structure/function were identified. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Tityus fasciolatus scorpion venom; Toxins; Anti-T. fasciolatus sera; Epitope mapping